Protest Politics in the Marketplace : Consumer Activism in the Corporate Age - Heldman, Caroline, 1972- (Book collections on Project MUSE., 2017)
This book examines how social media has revolutionized the use and effectiveness of consumer activism. The author emphasizes that consumer activism is a democratizing force that improves political participation, self-governance, and the accountability of corporations and the government. She also investigates the use of these tactics by conservatives. This book analyzes the democratic implications of boycotting, socially responsible investing, social media campaigns, and direct consumer actions, highlighting the ways in which such consumer activism serves as a countervailing force against corporate power in politics. This book blends democratic theory with data, historical analysis, and coverage of consumer campaigns for civil rights, environmental conservation, animal rights, gender justice, LGBT rights, and other causes.